Sex-based differences in the anatomic distribution of cutaneous squamous cell carcinoma - Yuhree Kim, MD, MPH; Jessica Feng, BS; Katherine A. Su, MD; Maryam M. Asgari, MD, MPH (Wolters Kluwer, 2020)
Background: Cutaneous squamous cell carcinoma (cSCC) is the second most common malignancy in the United States, and its incidence is increasing. Ultraviolet radiation is the main environmental risk factor for cSCCs; thus, they tend to arise on sun-exposed skin. Most publications cite the head and neck as the predominant location for cSCCs, but these papers do not account for the differential anatomic predication of cSCCs by sex. No prior studies have examined the differential distribution of cSCCs by sex, particularly invasive cSCCs that have the potential for recurrence and metastasis. Objective: We examined the association between cSCC tumor features, including anatomic site and invasiveness, by key patient features, including age and sex. Methods: Using an institutional cSCC registry, we identified 618 non-Hispanic white patients diagnosed with 2,111 histologically-confirmed cSCCs between 2000-2016. Results: We found differential anatomic distributions of cSCC by patient sex. Men were more likely to have cSCCs arise on the head and neck (51.7%), whereas women were more likely to have cSCCs develop on the lower extremity (41.2%). Stratification by dichotomized age (younger [<65 years] vs. older [≥65 years]) revealed that nearly half of invasive cSCCs (47.7%) among older women arose on the lower extremities, whereas approximately half of the invasive cSCCs (52.4%) arose on the head and neck among older men. Conclusion: Lower extremities can be easily overlooked, particularly when practitioners perform waist-up-only skin examinations in time-limited settings. Understanding the anatomic predilection for invasive cSCCs by patient characteristics, including our findings, which suggest that the lower extremities are an important anatomic site for invasive cSCCs among women, can help further inform skin cancer screening and prevention efforts.